The concept of global citizenship and coexistence _ Between the Islamic and Western perceptions_ - sellami, ferhat; dif, ghania (Journal of Social Sciences and Humanities, 2025)
This study aims to shed the light on the concept of universal citizenship based on the idea of shared(commun) living anong individuals in human societies through displaying idealogical and methdolo.gical prototypes of the concept the study in cluded a reading ints the islamic histsry through thisplaying and discussing -sahifat el madena- that the prsphet -Mohamed Sala Allahu..- appraved himself in the construction of the civil state at the dawn of islam.the study also derived from the western modern udeology the definition of universal citizenship and the universal citizen as sought -Edgar Moran- who is considred as one of it as leaders and the advacat to concel the patristic restrictions and empowering the interest of the universal human without its alienation of his individual and patristic specifity .